Myopic Shift After the Administration of Omidenepag Isopropyl in Patients with Normal-Tension Glaucoma - Kenji Inoue; Shiho Kunimatsu-Sanuki; Kyoko Ishida; Goji Tomita; Goji Tomita (Re:GEN Open, 2023)
Purpose: To evaluate myopic shift after the administration of omidenepag isopropyl (OMDI) in patients with normal-tension glaucoma (NTG).